Baldwin's harlem eaudiobook A biography of james baldwin. - Boyd, Herb (Recorded Books Inc., 2014)
Award-winning journalist Herb Boyd, author of Sugar Ray Robinson's biography Pound for Pound, combines impeccable research with astute literary criticism in Baldwin's Harlem. Packed with telling anecdotes, this concise volume illuminates Baldwin's diverse views and his impressions of the community that would remain a consistent presence in virtually all his writing.